Rights and obligations of participants in administrative procedures in international protection - Герасименко, Євгеній Станіславович; Герасименко, Є. С.; Герасименко, Евгений Станиславович; Herasymenko, Yevhenii S.; Gerasymenko, Yevgen S.; Задирака, Наталія Юріївна; Задирака, Н. Ю.; Задирака, Наталия Юрьевна; Zadyraka, Nataliia Yu.; Погребняк, Інга Василівна; Погребняк, І. В.; Погребняк, Инга Васильевна; et al. (SAGE Publications, 2021)
The rights and obligations of the state represented by the corresponding body or official are not specifically highlighted in the Directive. The certainty of some duties of the “representative” of the state can be concluded only by analysing the scope of refugee rights, because the procedural rights of a refugee are positive and for their implementation the state is obliged to take certain measures, otherwise these rights cannot be exercised. Consequently, the obligations of the state, represented by authorised persons, correspond to the rights of a refugee: if a refugee, for example, has the right to remain in the territory of the asylum state, the state must ensure that such refugee enjoys this right, including the non- refoulment of such a refugee from the asylum state. Therewith, certain procedural rights and obligations of participants in proceedings are specifically defined, and states can only expand their scope, or the scope of their guarantees. Other rights, obligations, mechanisms for their implementation or restrictions are relatively defined and are formulated in the form of the rights or powers of member states to implement them in national legislation. Consequently, in the Directive, next to specifically determined rules on the legal status of participants in the procedure, there are authorising and allowable provisions, which authorise or allow states to independently determine the elements of this legal status.

Права та обов'язки держави в особі відповідного органу чи посадової особи в Директиві спеціально не висвітлені. Про безсумнівність деяких обов’язків «представника» держави можна зробити висновок, лише аналізуючи обсяг прав біженця, оскільки процесуальні права біженця позитивні і для їх реалізації держава зобов’язана вжити певних заходів, інакше ці права не можна реалізувати. Отже, обов'язки держави в особі уповноважених осіб відповідають правам біженця: якщо біженець, наприклад, має право залишатися на території держави-притулку, держава повинна забезпечити, щоб такий біженець користувався цим правом, включаючи невисилання такого біженця з держави-притулку. При цьому окремо визначені певні процесуальні права та обов'язки учасників процесу, і держави можуть лише розширити їх сферу, або сферу своїх гарантій. Інші права, обов'язки, механізми їх реалізації чи обмежень є відносно визначеними і сформульовані у вигляді прав чи повноважень держав-членів щодо їх реалізації у національному законодавстві. Отже, в Директиві, поряд із спеціально визначеними правилами щодо правового статусу учасників процедури, є дозвільні та допустимі положення, які уповноважують або дозволяють державам самостійно визначати елементи цього правового статусу.
Gerasymenko Y. Rights and obligations of participants in administrative procedures in international protection / Y. Gerasymenko, N. Zadyraka, I. Pohrebniak, L. Zabolotna, I. Maslii // Public Policy and Administration. - Vol. 20(5). - SAGE Publications, 2021. - Р. 646-656.
Keywords: directive; administrative procedures; international protection; European Union; legislation; директива; адміністративні процедури; міжнародний захист; Європейський Союз; законодавство; Research Subject Categories::LAW/JURISPRUDENCE